Faktor budaya "hatuka ha'i" dalam perawatan masa nifas - Viktor Fahik, Wahyudi Istiono dan Wenny Artanty (Berita Kedokteran Masyarakat (BKM), 2004)
Background: National statistics show that 7% of childbirths were given at midwife house and 19% in hospital or private clinics. In NTT 70% of childbirths were given at home and half of these were assisted by traditional birth attendants and the family. Whereas at Belu District 39,43% of childbirths were assisted by health practitioners and 60,57% by traditional birth attendants and the family at home. This figure has significantly changed since 2003, in which 85,5% of childbirths were assisted by health practitioners and 13,5% by traditional birth attendants. However, the fact proves that there are lots of mothers who are assisted by traditional birth attendants and family during childbirth who practice Hatuka ha'i. Hatuka ha'i is a care given during traditional puerperal period by Tetun Tribe of Belu District, whereby for 40 days a mother and her newly born baby have to stay close to a fireplace and are not allowed to go out of the house. The mother has to eat warm foods, have warm drink and take a bath using warm water. Methods: The subject of the study was mothers during puerperal period who practice Hatuka ha'i. The study used a qualitative descriptive method. The sample includes mothers having practiced Hatuka ha'i. The variables of the study were Hatuka ha'i cultural factors. Results: The reasons why mothers and the family practiced Hatuka ha'i include economic factor, support from the family, convenience, normal pregnancy and previous experience with Hatuka ha'i. Whereas the following were Hatuka ha'i phenomena: the house for giving birth was closed and did not have ventilation, the fireplace was made to keep mothers and babies warm, mothers were restricted from activities and movement during Hatuka ha'i, mothers were not allowed to go out of the house and do other activities, there was restriction to certain food, and mothers were to eat boiled corn only, and mothers and their babies had to stay close to a fireplace for 40 days of Hatuka ha'i. Keywords: Hatuka ha'i, parturition, Tetun Tribe, puerperal period